Impact of ICT on virtual learning - Macias-Silva, Evelyn Carolina; Aquino-Rojas, Marco Antonio; Rodríguez-Pillajo, Lucio Armando; Heredia-Arboleda, Edgar Eduardo (Dominio de las Ciencias, 2020)
Information and Communication Technology (ICT) has transformed over time and is a promising tool for improving the learning process. The core aim of the research study is to evaluate the possibilities of teaching and learning in a virtual learning (networked) environment where both teachers and learners transform. This study relied on a literature review for forming a conclusion about the issue. The review of different articles revealed that ICT focuses on providing quality education, distance learning, low-cost learning, feedback option, and the option to record the session. The negative elements are that the connection may break due to poor internet, noise issues, inability to receive questions properly during the lecture, poor engagement with virtual learners, and deficient examination evaluation. Teachers and learners can transform by considering both the positive and negative sides of the ICT and having a back-up to avoid interruption in the learning session. It is concluded that the advent of smartphones, computers, laptops, and applications like Zoom, YouTube, Facebook, and WhatsApp video is transforming conventional teaching practices. The most common software is ‘Zoom’ in the current environment that encourages the learners to take sessions online. However, it also has drawbacks that have already been discussed. Hence, it is concluded that teachers and learners should consider both benefits and drawbacks of ICT when utilizing a virtual-learning session.